Helix 6 of subdomain III A of human serum albumin is the region primarily photolabeled by ketoprofen, an arylpropionic acid NSAID containing a benzophenone moiety - Chuang, Victor; Kuniyasu, A.; Nakayama, H.; Matsushita, Y.; Hirono, S.; Otagiri, M (Elsevier, 1999)
It is well known that the subdomain III A (site II) of human serum albumin (HSA) binds a variety of endogenous and exogenous substances. However, the nature of the microenvironment of the binding site remains unclear. Ketoprofen (KP), an arylpropionic acid NSAID which contains a benzophenone moiety, was used as a photoaffinity labeling agent to label the binding region. Subsequent CNBr cleavage of the photolabeled HSA revealed that the 11.6 kDa and 9.4 kDa fragments contained most of the incorporated radioactivity. Competition experiments showed that the 11.6 kDa fragment contains the common binding region for site II ligands. This fragment was redigested with Achromobacter lyticus protease I (AP-I) and the amino acid sequence of the photolabeled peptide was determined to be XCTESLVNRR, which corresponds to the sequence 476C-485K of HSA. The complete amino acid sequence of the corresponding AP-I digested HSA peptide encompasses residues 476 to 499, which form helices 5 and 6 of subdomain III A. The HSA-Myr X-ray crystallography data showed that helix 5 is involved to the least extent in ligand binding. A docking model provided further support that helix 6 represents the photolabeled region of KP.